2021
DOI: 10.21608/ejnf.2021.170304
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yeast (Saccharomyces Cerevisae), Garlic (Allium Sativum) and Their Combination as Feed Additives in Finishing Diets on the Performance, Ruminal Fermentation, and Immune Status of Lambs

Abstract: our groups of male lambs (seven animals/ group) were used to study the effect of natural (garlic powder; Allium sativum) and biological (dry yeast; Saccharomyces cerevisiae) additives and their combination in finishing diets as compared to control diet on feed utilization and animal performance. Animals were 8 months of age and 35.8kg ± 0. 41 as average body weight. Animals were fed a basal diet including concentrate feed mixture (CFM) at level of 70% of total requirement and berseem hay (BH) was offered ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 67 publications
3
11
1
Order By: Relevance
“…These results are in agreement with Van Soest [44] , who indicated that a high grain diet with soluble carbohydrate increase the passage rate and decline the rumen pH, which inhibits the rumen methanogens. The present result of loss of energy expressed was lower than that recorded for growing lambs (21.15%) fed berseem hay supplemented with concentrate feed mixture [45] .…”
Section: Discussioncontrasting
confidence: 86%
“…These results are in agreement with Van Soest [44] , who indicated that a high grain diet with soluble carbohydrate increase the passage rate and decline the rumen pH, which inhibits the rumen methanogens. The present result of loss of energy expressed was lower than that recorded for growing lambs (21.15%) fed berseem hay supplemented with concentrate feed mixture [45] .…”
Section: Discussioncontrasting
confidence: 86%
“…In line with our finding, the concentration of blood immunoglobulin (IgG) was enhanced by the inclusion of a YGM in diets of lamb (Kewan et al 2021). Likewise, Bilal et al (2021) found that yeast increased serum immunoglobulin (IgA) levels, which had a favorable effect on humoral immunity.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have shown that yeast culture (YC), as well as garlic extract (GE), improves abdominal health conditions; this could lead to increased nutrient utilization and digestibility in monogastric animals. Previous research found that yeast (S. cerevisiae), garlic (A. sativum), and their combination as feed additives in lamb finishing diets increased DM digestibility, E, and N in yeast-garlic mixed feed (Kewan et al 2021). Besides, S. cerevisiae inclusion in diet improved the E digestibility (Chen et al 2009) in broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition and contents of bioactive compounds in garlic products vary depending on the genotype, cultivation practices, growing conditions, plant density, soil type, fertilizer application rate and processing method of those products ( Chen et al., 2019 ; Kewan et al., 2021 ; Petropoulos et al., 2018 ). A summary of the characteristic chemical composition and contents of bioactive compounds in garlic products is provided in Table 1 .…”
Section: Chemical Composition and Bioactive Compounds Of Garlic Productsmentioning
confidence: 99%